2016
DOI: 10.1016/j.steroids.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

A new quantitation method of protodioscin by HPLC–ESI-MS/MS in rat plasma and its application to the pharmacokinetic study

Abstract: A specific high performance liquid chromatography tandem mass spectrometry (HPLC–MS/MS method) was established for determining the concentration of protodioscin (PG) in rat plasma after intragastric administration of its standard form. Ginsenoside Rb1 was selected as the internal standard (IS). The plasma sample was prepared using one-step deproteinization procedure by adding three parts of acetonitrile to precipitate proteins. The chromatographic separation was accomplished on an Inersil ODS-3 C18 column (250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Studies regarding the pharmacokinetic characteristics of protodioscin have contradictory results. For example, a recent study published by Zhang et al [52] concluded that protodioscin had low bioavailability in vivo. However, the same group of authors has shown that after the administration of an extract from Dioscorea, the pharmacokinetic profile of protodioscin revealed good bioavailability [53].…”
Section: Pharmacokinetic Properties Of Tt Main Compoundsmentioning
confidence: 99%
“…Studies regarding the pharmacokinetic characteristics of protodioscin have contradictory results. For example, a recent study published by Zhang et al [52] concluded that protodioscin had low bioavailability in vivo. However, the same group of authors has shown that after the administration of an extract from Dioscorea, the pharmacokinetic profile of protodioscin revealed good bioavailability [53].…”
Section: Pharmacokinetic Properties Of Tt Main Compoundsmentioning
confidence: 99%
“…Steroid saponins were a type of intensively polar compounds led by the constituent sugar groups and they except for their metabolites could pass through the membrane. However, this ability was weak and trace of them was determined in blood, therefore, our previous reports have demonstrated that they displayed a low bioavailability after oral administration of TSSN from D. zingiberensis [13, 31, 32]. We hypothesized another possibility that the concentration of steroid saponins in blood, tissue and organs couldn’t reach threshold values to cause the claimed toxic responses due to their low bioavailability pharmacokinetic features indicating the lack of toxicity of TSSN.…”
Section: Discussionmentioning
confidence: 93%
“…The main parameters were as follows: capillary voltage: 3000 V; source temperature: 150 °C; desolvation temperature: 300 °C; desolvation gas flow: 800 L/h; cone gas flow: 150 L/h; nebulizer gas flow: 7 bar; collision gas flow: 0.15 mL/min; cone voltage: 35 V and 28 V for RPDQ and IS, respectively; collision energy: 10 eV and 6 eV for RPDQ and IS, respectively. Masslynx V4.1 workstation (Waters, Milford, MA, USA) was used for data acquisition and processing [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%